Preparation method of CuFeTe2 film for solar cell
CuFeTe2 thin films were prepared by electrodeposition method and the annealing conditions were optimized, which solved the problem that the performance and crystal orientation of CuFeTe2 thin films in the prior art was affected by the annealing temperature, and achieved the optimal orientation of the film on the (101) crystal plane, significantly improved the crystal structure and deposition effect, and improved the performance of solar cells.
Patent Information
- Application Number
- CN202411574772.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-18
AI Technical Summary
Existing solar cell materials have challenges in improving photoelectric conversion efficiency and reducing material costs, especially in the preparation of CuFeTe2 films, the selection of annealing temperature has a significant impact on performance and crystal orientation.
CuFeTe2 films were prepared by electrodeposition method. By controlling electrochemical potential and current process parameters, the thickness, chemical composition and crystal structure of the film were accurately controlled, and annealed at specific temperatures and time to optimize the performance and crystal orientation of the film.
By optimizing the deposition potential and annealing conditions, the CuFeTe2 film forms an optimal orientation on the (101) crystal plane, significantly improving the crystal structure of the film, improving the continuous density and deposition effect of the film, thereby improving the performance of solar cells.
Smart Images

Figure CN119653891A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar energy and relates to a method for preparing a CuFeTe2 film for a solar cell. Background Art
[0002] In recent years, the use of non-renewable energy such as coal, oil, and natural gas has increased. Large-scale mining and use will make humans face the crisis of non-renewable energy depletion, and will also bring certain environmental pollution problems and aggravate the greenhouse effect. Based on this, the development of new energy is particularly important. As an inexhaustible renewable energy source, solar energy has attracted widespread attention. Solar cells are devices that convert sunlight into electrical energy, and their development history can be traced back to the 19th century. With the development of science and technology, solar cell technology has been continuously optimized, and many types of solar cells have emerged, such as silicon-based solar cells, cadmium telluride (CdTe) thin film cells, copper indium gallium selenide (CIGS) thin film cells, copper zinc tin sulfur (CZTS) thin film cells, gallium arsenide (GaAs) thin film cells, dye-sensitized thin film cells, etc.
[0003] Although there are many types of existing solar cells, they all have corresponding problems at present, because new thin-film solar cell materials need to be developed to further improve the photoelectric conversion efficiency and reduce the material cost, such as optimizing the material of the P-type absorption layer, and matching the corresponding preparation method of the P-type absorption layer, such as: chemical co-reduction, magnetron sputtering, vacuum evaporation, hydrothermal or electrodeposition method. CuFeTe2 is a typical two-dimensional ternary transition metal silicide, which exhibits fuzzy magnetic behavior and spin density wave characteristics in the ground state. This is a very narrow band gap, and can even reach 0 band gap. CuFeTe2 is a crystal with tetragonal crystals, and its lattice constants are a=b=3.934A, c=6.078A, and p=P4 / nmm. CuFeTe2 is a promising P-type semiconductor material.
[0004] Since the absorption layer material has certain requirements for its composition ratio, different preparation methods will lead to different compositions and structures of the prepared films, resulting in different electrical and optical properties, leading to changes in battery efficiency. In particular, the choice of annealing temperature after electrodeposition of the film affects its performance.
[0005] Based on the above research, it is necessary to provide a method for preparing CuFeTe2 thin film for solar cells. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a CuFeTe2 thin film for solar cells. The electrodeposition method is a process of depositing materials on an electrode using an external power source. The quality of the film is guaranteed by controlling process parameters such as electrochemical potential and current, and the thickness, chemical composition and crystal structure of the film are accurately controlled. However, the film after electrodeposition needs to be annealed at a specific temperature, which affects the performance and crystal orientation of the electrodeposited film.
[0007] Flow chart of electrodeposition preparation of copper iron tellurium thin film. Electrodeposition preparation process: experimental drug preparation - FTO base cleaning (preparation of electrodeposition solution) - constant potential deposition - heat treatment - target product film.
[0008] FTO base cleaning: The main cleaning process of FTO substrate is as follows: S1: Use medical cloth to clean the FTO base to remove dust and grease remaining on its surface; S2: Put the FTO base into a detergent solution for ultrasonic cleaning for 10 minutes; S3: Put the FTO base into deionized water for ultrasonic cleaning for 10 minutes; S4: Then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 for ultrasonic cleaning for 10 minutes; S5: Put it into anhydrous ethanol for ultrasonic shock for 10 minutes; S6: Finally, put the cleaned FTO base into anhydrous ethanol for storage, wrap the beaker mouth with plastic wrap and seal it.
[0009] Preparation of electrodeposition solution: The steps for preparing the electrodeposition solution are as follows: weighing the drug using an analytical balance, dissolving tellurium dioxide in hydrochloric acid, using a magnetic stirrer to heat and stir the solution to accelerate its dissolution, and after the dissolution is completed, adding deionized water to a preset scale, and then adding sodium citrate, FeCl2 and CuSO4, fully dissolving them, and finally obtaining an electrodeposition solution.
[0010] Sample preparation and preservation, heat treatment: The film was prepared at atmospheric pressure and electrodeposited using a three-electrode system with constant potential. The FTO glass substrate was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the electrode was a platinum electrode. According to different research schemes, the electrodeposition solution was configured, and the temperature of the solution during the deposition process was controlled by a water bath. At the end of the deposition, the substrate coated with the target product was removed from the precipitation solution, soaked in deionized water three times, and then dried in an incubator. The sample was sealed in a steel reactor and annealed at a fixed temperature and time. After annealing, the sample was cooled to room temperature and stored in a sample bag.
[0011] To achieve the purpose of the invention, the present invention adopts the following technical solution: a method for preparing a CuFeTe2 thin film for a solar cell, characterized in that it comprises the following steps: FTO substrate cleaning step and electrodeposition solution preparation step: the electrodeposition solution comprises; Constant potential deposition step: under atmospheric pressure, the FTO base is placed in an electrodeposition solution for electrodeposition using a constant potential three-electrode system, and the deposition temperature, deposition time and deposition potential are preset, and the deposition potential is -1.0V; wherein the FTO base is a working electrode, a saturated calomel electrode is used as a reference electrode, the electrode is a platinum electrode, and the temperature of the electrodeposition solution is controlled by a water bath method; Cleaning and annealing steps: The sample treated in the constant potential deposition step is immersed in deionized water for three times, then taken out and annealed at a preset temperature and a preset time to prepare a CuFeTe2 film.
[0012] FTO base cleaning includes: S1: Use a medical cloth to clean the FTO base and remove the dust and grease remaining on its surface; S2: placing the FTO base in a detergent solution for ultrasonic cleaning for 10 minutes; S3: placing the FTO base in deionized water for ultrasonic cleaning for 10 minutes; S4: then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 and perform ultrasonic cleaning for 10 minutes; S5: Place in anhydrous ethanol and ultrasonically impact for 10 minutes; S6: Finally, the cleaned FTO base is stored in anhydrous ethanol, and the beaker mouth is wrapped with plastic wrap and sealed. The steps of preparing the electrodeposition solution are to weigh the drug using an analytical balance, dissolve tellurium dioxide in hydrochloric acid, use a magnetic stirrer, stir and dissolve while heating to accelerate its dissolution, and after the dissolution is completed, add deionized water to the preset scale, and then add sodium citrate, FeCl2 and CuSO4, fully dissolve, and finally obtain the electrodeposition solution.
[0013] Preferably, the deposition time of the constant potential deposition step is 20 min.
[0014] Preferably, the deposition temperature of the constant potential deposition step is 30° C. and the deposition time is 20 min.
[0015] Preferably, the deposition temperature of the constant potential deposition step is 50° C. and the deposition time is 20 min.
[0016] Preferably, the thickness of the CuFeTe2 film is 20 μm.
[0017] Preferably, the deposition temperature of the constant potential deposition step is 90° C. and the deposition time is 20 min.
[0018] Preferably, in the annealing step, the preset temperature is 200° C., and the preset time is 30 hours.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The solar cell of the present invention is a thin-film solar cell based on copper iron telluride (CuFeTe2). CuFeTe2 is a layered material with p-type semiconductor characteristics. By optimizing the deposition potential and optimizing the annealing time and annealing temperature (annealing at 220°C for 20h), the CuFeTe2 film forms a preferred orientation on the (101) crystal plane, significantly improving the crystal structure of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of films deposited at -1.0 V and -0.9 V, annealed at 220 °C (top), 150 °C (middle), and not annealed (bottom). DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0022] In order to analyze the electrodeposition process of the film, the effect of different complexing agents on the solution was studied by cyclic voltammetry. Disodium EDTA, oxalic acid, sodium citrate and potassium sodium tartrate were selected as complexing agents, respectively, and tested with a CHI760e electrochemical workstation at room temperature. A platinum electrode was used as an auxiliary level, a platinum electrode was used as an auxiliary electrode, and a SCE saturated calomel electrode (KCl) with about +0.245V was used as a reference electrode. The scanning voltage range was +0V to -1.0V, and a negative scan was performed first, followed by a positive scan, with a scan rate of 10mV / s.
[0023] A method for preparing a CuFeTe2 thin film for a solar cell, characterized in that it comprises the following steps: FTO substrate cleaning step and electrodeposition solution preparation step: the electrodeposition solution comprises; Constant potential deposition step: under atmospheric pressure, the FTO base is placed in an electrodeposition solution for electrodeposition using a constant potential three-electrode system, and the deposition temperature, deposition time and deposition potential are preset, and the deposition potential is -1.0V; wherein the FTO base is a working electrode, a saturated calomel electrode is used as a reference electrode, the electrode is a platinum electrode, and the temperature of the electrodeposition solution is controlled by a water bath method; Cleaning and annealing steps: The sample treated in the constant potential deposition step is immersed in deionized water for three times, then taken out and annealed at a preset temperature and a preset time to prepare a CuFeTe2 film.
[0024] FTO base cleaning includes: S1: Use a medical cloth to clean the FTO base and remove the dust and grease remaining on its surface; S2: placing the FTO base in a detergent solution for ultrasonic cleaning for 10 minutes; S3: placing the FTO base in deionized water for ultrasonic cleaning for 10 minutes; S4: then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 and perform ultrasonic cleaning for 10 minutes; S5: Place in anhydrous ethanol and ultrasonically impact for 10 minutes; S6: Finally, the cleaned FTO base is stored in anhydrous ethanol, and the beaker mouth is wrapped with plastic wrap and sealed. The steps of preparing the electrodeposition solution are to weigh the drug using an analytical balance, dissolve tellurium dioxide in hydrochloric acid, use a magnetic stirrer, stir and dissolve while heating to accelerate its dissolution, and after the dissolution is completed, add deionized water to the preset scale, and then add sodium citrate, FeCl2 and CuSO4, fully dissolve, and finally obtain the electrodeposition solution.
[0025] In some specific embodiments, the deposition time of the constant potential deposition step is 20 min.
[0026] In some specific embodiments, the deposition temperature of the constant potential deposition step is 30° C., and the deposition time is 20 min.
[0027] In some specific embodiments, the deposition temperature of the constant potential deposition step is 50° C., and the deposition time is 20 min.
[0028] In some specific embodiments, the thickness of the CuFeTe2 film is 20 μm.
[0029] In some specific embodiments, the deposition temperature of the constant potential deposition step is 90° C., and the deposition time is 20 min.
[0030] In some specific embodiments, in the annealing step, the preset temperature is 200° C., and the preset time is 30 hours.
[0031] A preparation method for a solar cell, the sequence is: conductive oxide glass substrate, ZnO layer, TiO2 electron transport layer, P-type CuFeTe2 absorption layer, hole transport layer and back electrode layer; the thickness of the TiO2 electron transport layer is 70nm-90nm, and the thickness of the P-type CuFeTe2 absorption layer is 20μm. The conductive oxide glass substrate is FTO conductive glass or ITO ultra-white glass.
[0032] The hole transport layer is prepared by spin coating, including: dissolving Spiro-OMeTAD in chlorobenzene, continuing to add 4-tert-butylpyridine and Li-TFSI acetonitrile solution and stirring until the solution is clear and transparent, spin coating the prepared Spiro-OMeTAD solution on the surface of the above-mentioned P-type CuFeTe2 absorption layer, and then placing it on a heating plate and heating it at 110°C in air for 15 minutes. The material of the back electrode layer is gold, and the thickness of the back electrode layer is 80nm-90nm. The thickness of the P-type CuFeTe2 absorption layer is 20μm, and the P-type CuFeTe2 absorption layer is deposited on the surface of the TiO2 electron transport layer by electrodeposition. Conductive oxide glass substrate, ZnO layer, TiO2 electron transport layer, P-type CuFeTe2 absorption layer, hole transport layer and back electrode layer.
[0033] Preparation of ZnO layer: deposit a 80nm-85nm ZnO electron transport layer by sol-gel method; preparation of TiO2 electron transport layer: add 70uL of dilute hydrochloric acid and 700uL of isopropyl titanate to 5ml of ethanol respectively, and then mix them together to obtain TiO2 solution. After sufficient mixing and shaking, filter and set aside; then statically drop the filtered TiO2 solution onto the ZnO layer, spin coat at 2000rpm for 30s, and heat and anneal at 150℃, 250℃, and 350℃ for 10min respectively, and finally heat and anneal at 550℃ for 30min to obtain an electron transport layer (TiO2) film with a thickness of about 50nm; P-type CuFeTe2 absorption layer is prepared by electrodeposition method.
[0034] like Figure 1 As shown, when the deposition potential is -1.0V and -0.9V, the deposition temperature is 50℃, the deposition time is 20min, the annealing temperature is 220℃ / 20h (upper figure), 150℃ / 20h (middle figure) and the unannealed (lower figure) film XRD patterns, among which, therefore, in the film prepared by electrodeposition, by controlling the annealing temperature and time, the deposition time can be controlled to obtain a better deposition effect.
[0035] XRD patterns of samples withdrawn after electrodeposition at different deposition potentials when the deposition temperature is 30℃ and the deposition time is 20min. When the deposition potential is -0.6V, the diffraction peak of CuFeTe2 gradually appears, and the diffraction peak gradually increases with the negative shift of the deposition potential. Except that the diffraction peak of CuFeTe2 does not appear when the deposition potential is -0.9V, when the deposition potential is -1.0V, the diffraction peak intensity reaches the maximum value and then gradually decreases. Corresponding to the standard spectrum (PDF standard card No. 70-3094), the diffraction peak of CuFeTe2 grows along the (101), (112) and (211) crystal planes, and the diffraction angles are 2θ=26.975°, 44.097° and 54.233°, respectively. The film forms a preferred orientation on the (101) crystal plane. In addition to the target product CuFeTe2, the diffraction peak of SnO2 was also found (PDF standard card No. 46-1088). At the same time, as the deposition potential shifts negatively, the hydrogen evolution phenomenon will intensify, it is not easy to form a continuous film, the porous bonding force of the film is poor, and black particles appear near the working electrode suspended on the surface of the solution. Therefore, when the deposition temperature is 30°C, the deposition time is 20min, and the deposition potential is -1.0V, the deposition effect is the best.
[0036] Furthermore, when the deposition temperature is 50℃ and the deposition time is 20min, the peak diffraction value of CuFeTe2 gradually appears at the deposition potential of -0.6V and -0.7V for the samples that were electrodeposited at different deposition potentials and then heat treated. The diffraction peak of the film increases with the negative shift of the deposition potential, and the deposition voltage is the largest at -1.0V. Corresponding to the standard spectrum (PDF standard card No. 70-3094), the diffraction peak of CuFeTe2 grows along the (101), (112) and (211) crystal planes, and the diffraction angles are 2θ=26.975°, 44.097° and 54.233°, respectively. The film forms a preferred orientation on the (101) crystal plane. In addition to the target product CuFeTe2, the diffraction peak of SnO2 was also found (PDF standard card No. 46-1088). Therefore, when the deposition temperature is 50℃ and the deposition time is 20min, the deposition effect is best when the deposition potential is -1.0V.
[0037] Therefore, by controlling the deposition potential to -1.0 V, the CuFeTe2 film forms a preferred orientation on the (101) crystal plane, which significantly improves the crystal structure of the film, makes the film continuous and dense within a certain range, and achieves the best deposition effect.
[0038] Furthermore, by preparing a solar cell containing a CuFeTe2 thin film, the performance of the solar cell can be effectively improved because the higher the film orientation, the better the performance of the solar cell.
[0039] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a CuFeTe2 thin film for solar cells, characterized in that: The steps include: FTO substrate cleaning steps and electrodeposition solution preparation steps; Constant potential deposition step: under atmospheric pressure, a three-electrode system with a constant potential is used to place the FTO base in an electrodeposition solution for electrodeposition, the deposition temperature is 50°C, the deposition time is 20 minutes, and the deposition potential is -1.0V or -0.9V; wherein the FTO base is a working electrode, a saturated calomel electrode is used as a reference electrode, the electrode is a platinum electrode, and the temperature of the electrodeposition solution is controlled by a water bath method; Cleaning and annealing step: soaking the sample after the constant potential deposition step in deionized water, then taking it out, and then performing an annealing step to prepare a CuFeTe2 film; The annealing step is performed at 220° C. for 20 hours.
2. The method for preparing a CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The deposition potential was -1.0V.
3. The method for preparing a CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The solvent of the electrodeposition solution is hydrochloric acid.
4. The method for preparing a CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The deposition potential was -0.9V.
5. The method for preparing a CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The steps of preparing the electrodeposition solution are as follows: weighing the drug using an analytical balance, dissolving tellurium dioxide in hydrochloric acid, using a magnetic stirrer to heat and stir the solution to accelerate its dissolution, adding deionized water to a preset scale after the solution is completed, and then adding sodium citrate, FeCl2 and CuSO4 to fully dissolve the solution to obtain the electrodeposition solution.
6. The method for preparing a CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The thickness of the CuFeTe2 film is 20 μm.
7. The method for preparing a CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The deposition temperature of the constant potential deposition step is 90° C., and the deposition time is 20 min.
8. The method for preparing a CuFeTe2 thin film for solar cells according to claim 1, characterized in that: The FTO base cleaning includes: S1: Use a medical cloth to clean the FTO base and remove the dust and grease remaining on its surface; S2: placing the FTO base in a detergent solution for ultrasonic cleaning for 10 minutes; S3: placing the FTO base in deionized water for ultrasonic cleaning for 10 minutes; S4: then put it into a solution of anhydrous ethanol and deionized water with a mixing ratio of 1:1 and perform ultrasonic cleaning for 10 minutes; S5: Place in anhydrous ethanol and ultrasonically impact for 10 minutes; S6: Finally, the cleaned FTO base is stored in anhydrous ethanol, and the mouth of the beaker is wrapped with plastic wrap and sealed.
Citation Information
Patent Citations
Synthesis method of two-dimensional material, two-dimensional material and application of two-dimensional material
CN115287743A